Sarcopenic obesity associated with high-sensitivity C-reactive protein in age and sex comparison: a two-center study in South Korea. Issue 9 (19th September 2018) - Park, Chul-Hyun; Do, Jong Geol; Lee, Yong-Taek; Yoon, Kyung Jae
Abstract : Objectives: To evaluate the association between high-sensitivity C-reactive protein (hs-CRP) and sarcopenic obesity, and to determine age or sex differences underlying the relationship between hs-CRP and sarcopenic obesity. Design: Observational study. Participants: The study included 237 838 participants whose body composition and hs-CRP were analysed at the two health promotion centres in South Korea. Participants were divided into four groups based on body composition: normal, obesity only, sarcopenia only and sarcopenic obesity. Primary measures: The levels of hs-CRP and proportion of participants with high (≥1.0 mg/L) hs-CRP. Sarcopenic obesity was defined as subjects fulfilling the criteria for sarcopenia (below 2 SD of mean of Skeletal Muscle Mass Index for young adults) and obesity (waist circumference ≥90 cm for men and ≥85 cm for women). Results: The level of hs-CRP was highest in the sarcopenic obesity group. Following adjustment for various confounders including age, sex, comorbidities, metabolic, health-related behaviour and demographic factors, the adjusted ORs (95% CI) for subjects with high hs-CRP associated with obesity, sarcopenia and sarcopenic obesity compared with normal group (reference) were 1.17 (1.05 to 1.31), 2.23 (1.21 to 4.07) and 3.23 (2.71 to 3.83), respectively. In age subgroup analyses, multivariate logistic regression analysis revealed that the association of high hs-CRP with sarcopenic obesity was stronger in younger (<60 years) participants than in older (≥60 years) participants (p for interaction <0.001). In subgroup analyses for sex, the association of high hs-CRP with sarcopenic obesity was higher in female participants than in males (p for interaction <0.001). Conclusions: This study demonstrated that high level of hs-CRP was independently associated with sarcopenic obesity in Korean population. We found for the first time that there was a strong association between increased hs-CRP and sarcopenic obesity in female and younger (<60 years) subjects.